Annotated bird sighting list, Fall 1980 compiled by Raymond L. Cummins - Cummins, Raymond L.et al (1980)
An annotated bird sighting list for Fall from Raymond L. Cummins, dated November 26, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed